Analytical characterization of N,N-diallyltryptamine (DALT) and 16 ring-substituted derivatives - Brandt, Simon D.; Meyer, Markus Robert (Drug testing and analysis, 2017)
Many N,N-dialkylated tryptamines show psychoactive properties in humans and the number of derivatives involved in multidisciplinary areas of research has grown over the last few decades. Whereas some derivatives form the basis of a range of medicinal products, others are predominantly encountered as recreational drugs, and in some cases, the areas of therapeutic and recreational use can overlap. In recent years, 5-methoxy-N,N-diallyltryptamine (5-MeO-DALT) has appeared as a new psychoactive substance (NPS) and ‘research chemical’ whereas 4-acetoxy-DALT and the ring-unsubstituted DALT have only been detected very recently. Strategies pursued in the authors' laboratories included the preparation and biological evaluation of previously unreported N,N-diallyltryptamines (DALTs). This report describes the analytical characterization of 17 DALTs. Fifteen DALTs were prepared by a microwave-accelerated Speeter and Anthony procedure following established procedures developed previously in the authors' laboratories. In addition to DALT, the substances included in this study were 2-phenyl-, 4-acetoxy-, 4-hydroxy-, 4,5-ethylenedioxy-, 5-methyl-, 5-methoxy-, 5-methoxy-2-methyl-, 5-ethoxy-, 5-fluoro-, 5-fluoro-2-methyl-, 5-chloro-, 5-bromo-, 5,6-methylenedioxy-, 6-fluoro-, 7-methyl, and 7-ethyl-DALT, respectively. The DALTs were characterized by nuclear magnetic resonance spectroscopy (NMR), gas chromatography (GC) quadrupole and ion trap (EI/CI) mass spectrometry (MS), low and high mass accuracy MS/MS, photodiode array detection, and GC solid-state infrared analysis, respectively. A comprehensive collection of spectral data was obtained that are provided to research communities who face the challenge of encountering newly emerging substances where analytical data are not available. These data are also relevant to researchers who might wish to explore the clinical and non-clinical uses of these substances. Copyright © 2016 John Wiley & Sons, Ltd.
Published online in Wiley Online Library: 21 April 2016
Gesehen am 18.06.2018